2018
DOI: 10.3390/agronomy8040047
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Diurnal Carbohydrate Accumulation in White Clover (Trifolium repens L.)

Abstract: White clover (Trifolium repens L.) is one of the most important legumes for fodder production in temperate climates, particularly in intensive pasture systems. Like many other forage legumes, it lacks the energy content to maximize productivity of modern ruminant livestock breeds. White clover produces water-soluble carbohydrates and starch in its leaves as a diurnal product of photosynthesis. However, little is known about the genetically encoded variability of diel changes in carbohydrate content. We assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Previous results showed that biochanin A inhibited amylolytic bacteria, including Streptococcus bovis [8]. Typical forage legumes, like clovers, contain variable amounts of starch [41]. In C3 grasses, starch tends to be a smaller proportion of the nonstructural carbohydrate than fructan [42], although starch concentrations can be elevated at low temperatures [43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed that biochanin A inhibited amylolytic bacteria, including Streptococcus bovis [8]. Typical forage legumes, like clovers, contain variable amounts of starch [41]. In C3 grasses, starch tends to be a smaller proportion of the nonstructural carbohydrate than fructan [42], although starch concentrations can be elevated at low temperatures [43].…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for many years that increasing AGPase activity leads to increased starch synthesis, and as was mentioned above, increasing starch in food and fodder crops would improve their calorific value (Ruckle et al., 2017, 2018). However, interestingly, increasing starch amounts in this way can have beneficial effects on plant productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, although this was demonstrated convincingly in glasshouse trials (Ral et al., 2012; Bowerman et al., 2016), when the same lines were examined in the field a reduction in yield was observed (Whan et al., 2017). Although it may not be a valuable way to increase starch yield in storage organs, repressing genes involved in this process could improve forage and silage crops by improving their calorific value for animal feed (Weise et al., 2012; Ruckle et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Starch, sucrose, fructose and glucose contents were quantified as described in earlier studies (Ruckle et al, 2017 ; Ruckle, Bernasconi, Kölliker, Zeeman, & Studer, 2018 ). The flash‐frozen samples (see above) were lyophilized, and biomass was recorded as lyophilized leaf weight.…”
Section: Methodsmentioning
confidence: 99%